Intracranial hemorrhage in the shadows of infective endocarditis as a silent menace: a case report - Mohamed Shukor, Ahmad Zulkifli; Abidin, Mohd Radhwan; Zainulabid, Ummu Afeera (Bangladesh Infection Research Association, 2023)
It is surprising when a patient’s care-taker informed the doctor that their family member could suddenly speak in a different accent. Here we reported a case of a young female with infective endocarditis (IE), who later developed a foreign accent syndrome during her stay in the hospital ward. A plain computed tomography (CT) scan of the brain was performed and it showed a coarse and irregular calcific lesion in the left frontal region. Her condition deteriorated rapidly the next day and she died of intracranial haemorrhage. The haemorrhage was possibly caused by a ruptured mycotic aneurysm, a known complication of IE.